Phagocytic and metabolic activity of neutrophils of rats in the early stages of post-embryonic development under the influence of biologically active substances of the salt extract of Hirudo verbana - Aminov, R. F.; Frolov, A. K. (Regulatory Mechanisms in Biosystems, 2016)
The nitroblue tetrazolium test reflects the degree of activation of oxygen-dependent mechanisms of bactericidal activity of phagocytotic cells, so the increase in nbt-test and phagocytic indices shows increased activation in the bacterial process and enhanced protection with the help of the absorption ability of the cells in the body. We examined females of nonlinear rats after feeding of their offspring, which 2 weeks before and 2 weeks after mating were injected intraperitoneally with antigens of saline extract of medical leeches (4 injections) and the offspring at days 1, 15, 30, 45, 60. The dosage of salt extract antigens was carried out by determining the protein concentrations using the Lowry protein assay. The animals were immobilized using an immobilizing device. The animals were distributed into three groups: the first research and experimental group of animals was subject to the influence of medical leech salt extract antigens to the amount of 0.5 ml (at the rate of 3 µg/g of animal weight); the second group of intact animals was not subject to intervention, the third control group of animals was administered intraperitoneally saline 0.5 ml of 9% saline solution. We studied females after feeding offspring and offspring at 1, 15, 30, 60 days. The animals were kept in vivarium conditions in individual cages on a standard diet. In the experiment we used 60 females of non-linear rats and 300 of their offspring. All animals were decapitated under ether anesthesia. After that, we took blood, made a solution with crystal heparin and examined the laboratory parameters: total number of leukocytes and leukocyte formula. Evaluation of nonspecific resistance of the organism was investigated using tests which characterize the activity of neutrophils (nbt-test, phagocytosis indices). The results of our studies revealed a positive effect of antigens of saline extract of medical leeches on the absorptive and metabolic activity of neutrophils in the females and their offspring in all study periods compared with the control, an increased number of leukocytes, due to the change of the process of differentiation and deposition of cells in immunogenic organs on proliferation. Changes in immunological parameters indicate the immunostimulatory effect of AG ML on leukopoiesis and on the functional activity of neutrophils – the first line of defense against entry into the body of a variety of bacteria, fungi and protozoa.